SAE Technical Paper Series 2019
DOI: 10.4271/2019-01-0546
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Analysis of Steel and Aluminium Pistons for an HSDI Diesel Engine

Abstract: Chromium-molybdenum alloy steel pistons, which have been used in commercial vehicle applications for some time, have more recently been proposed as a means of improving thermal efficiency in lightduty applications. This work reports a comparison of the effects of geometrically similar aluminium and steel pistons on the combustion characteristics and energy flows on a single cylinder high-speed direct injection diesel research engine tested at two speed / load conditions (1500 rpm / 6.9 bar nIMEP and 2000 rpm /… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Increasing a coating's permeability has been shown to reduce thermal efficiency and increase heat losses as fuel/air mixture is trapped in the coating's pores as well as reducing the effective compression ratio [10,[14][15][16]. Furthermore, Kawaguchi et al [8] found that increased surface roughness results in reduced fuel spray penetration, which has been shown to lead to lower burn rates and reduced efficiency [17], although it must be noted that Kawaguchi et al did not model the combined effects of surface roughness and porosity.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing a coating's permeability has been shown to reduce thermal efficiency and increase heat losses as fuel/air mixture is trapped in the coating's pores as well as reducing the effective compression ratio [10,[14][15][16]. Furthermore, Kawaguchi et al [8] found that increased surface roughness results in reduced fuel spray penetration, which has been shown to lead to lower burn rates and reduced efficiency [17], although it must be noted that Kawaguchi et al did not model the combined effects of surface roughness and porosity.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, different piston materials, cylinder heads, injector types, nozzle types and injection strategies were all tested using a combination of the above parameters. The experimental findings for these configurations are detailed in literature [26,27]. Table 2 shows the engine configurations that were tested in this work, along with the baseline configuration.…”
Section: Experimental Apparatusmentioning
confidence: 99%
“…The dataset includes 7 months of engine testing from the University of Oxford single-cylinder diesel research engine. The engine and its test cell have been designed to give the highest quality data, [21][22][23] and much of this dataset has already been published. 4,22,24 Overall the dataset consisted of 1108 individual experiments.…”
Section: Introductionmentioning
confidence: 99%